Evaluation of heavy metal bioremediation potential using microbes from contaminated landfill soil / Nor Asni Abdullah - Nor Asni , Abdullah (2022)
Chemical evaluations and characterization had often served as the commonly adopted options for assessing the potential impact of pollutants, which at the same time provide insight into the possible remediation technologies. However, heterogeneous substances may not be best studied in aforementioned forms because of the varied characteristics and concentrations of discrete components. Considering the high distribution of waste disposal site in Malaysia, the study was designed to isolate and identify bacterial species from leachate polluted soil. This study also aimed to generate a blend of microbial inoculum with high heavy metal resistance to serve as potential combination for optimal bioremoval of heavy metal from contaminated sites. The study also was undertaken to assess heavy metal removal performance in monometal and polymetal systems. Last but not least was to evaluate the behavioral changes of microorganisms due to metal pollution. Various methods adopted in the study ranged from soil samples collection from selected contaminated soil, microbial isolation, microbial identification, microbial inoculum build up, preparation of heavy metal standard solutions and designing experiment based on monometal system and polymetal system. Microsoft Excel and SPSS were statistical tools used in the study. Results were recorded based on 2- and 8-Day incubation period for both monometal and polymetal system. Different treatments displayed varying capacity in heavy metal removal. In monometal system, the highest rate constant value for Treatment A was Pb (K= 0.370 day-1) while Treatment B is Fe (K= 0.338 day-1) and Treatment AB is Fe (K= 0.376 day-1) in two days. Meanwhile in eight days, the highest rate constant value for Treatment A is Mn (K= 0.178 day-1) while Treatment B is Fe (K= 0.095 day-1) and Treatment AB is Fe (K= 0.167 day-1). In polymetal system, the highest rate constant value for Treatment A is Pb (K= 0.550 day-1) and Treatment B also is Pb (K= 0.251 day-1) while Treatment AB is Ni (K= 1.242 day-1) in two days. Meanwhile in eight days, the highest rate constant value for Treatment A is Cr (K= 0.320 day-1) while Treatment B is Pb (K= 0.188 day-1) and Treatment AB is Pb (K= 0.067 day-1). These results suggested that there were complex interactions exist within the bacteria. The removal of heavy metal was also found to be dependent with exposure duration and metal complexity. In general, Gram-positive bacteria displayed a better heavy metal removal performance than Gram-negative bacteria. In the presence of heavy metals, Gram-positive and Gram-negative bacteria have different threshold of tolerance as reflected by their bacterial count and the final pH condition. Therefore, it can be concluded that different microbial blends have different optimal conditions to achieve the best heavy metal removal performance.